Perceived Stress, Severity of Asthma, and Quality of Life in Young Adults with Asthma - Tomoaki Kimura; Akihito Yokoyama; Nobuoki Kohno; Hiroyuki Nakamura; Akira Eboshida (Allergology International, 2009)
Background: People suffering from asthmatic symptoms have a lower quality of life than those without. The aim of this study is to clarify the association of quality of life with the severity of asthma, perceived stress, and other factors such as the comorbidity of allergic diseases among young adults with asthma. Methods: The study participants were 695 asthma patients, aged 20-44 years, from 29 medical centers in Japan. We excluded from the analysis of the result of the study 116 patients with complications of serious diseases, cough-variant asthma or aspirin-intolerant asthma. The patients completed the 8-Item Short-Form Health Survey (SF-8), the Airways Questionnaire 20 (AQ20), and the Japanese version of the Perceived Stress Scale (JPSS) and their doctors also provided clinical information including diagnosis, complications, severity of asthma, and results of pulmonary function and immunological tests. Results: There was a weak correlation between the generic quality of life (SF-8) and the disease-specific quality of life (AQ20). The AQ 20 revealed almost no association with the results of pulmonary function and immunological tests, and only a slight association with comorbidity of allergic rhinitis and food allergy. The AQ20 showed a moderate relation with perceived stress (JPSS) but a weak association with the severity of asthma. The multiple logistic models demonstrated that there was no relationship between the severity of asthma and the AQ20 in females, and in the age group of 20-34 years. Conclusions: A major variable related to the disease-specific quality of life was perceived stress, followed by the severity of asthma. Stress management of patients with asthma may improve their quality of life.